Providing a Causal Model of the Behavioral Disorders in Children Based on Child-Mother Interaction and Parental Acceptance with the Mediating Role of Life Satisfaction in Hyperactive Children’s Mothers in Tehran - Ghalenoee, Mahdie; Asadzadeh, Hassan; Dortaj, Fariborz (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Since hyperactive children are unable to control or dominate over their surroundings, they cannot achieve their wants or perform them, they show some symptoms of behavioral disorders. The purpose of the present study was to provide a causal model of children’s behavioral disorders based on child-mother interaction and parental acceptance with the mediating role of life satisfaction in hyperactive children’s mothers. Methods: This research was a descriptive correlational study performed by the path analysis method. The statistical population of the present study included all mothers of hyperactive children visiting psychiatric clinics in Tehran in 2020, out of whom 250 mothers were selected using purposive sampling. The research instruments included Children’s Behavioral Disorders Questionnaire (CBDQ), Child-Mother Interaction Questionnaire (CMIQ), Parental Acceptance Questionnaire (PAQ), and Life Satisfaction Questionnaire (LSQ). The proposed model was evaluated using Path Analysis by SPSS Amos 24.0. Results: The results showed that there is a positive and significant relationship between child-mother interaction/parental acceptance and life satisfaction. Moreover, there was an inverse and significant relationship between child-mother interaction and parental acceptance. The results also showed that the general parental acceptance path had a greater effect on hyperactive children’s behavioral disorders. Conclusions: The causal model of children’s behavioral disorders based on child-mother interaction and parental acceptance with the mediating role of life satisfaction in hyperactive children’s mothers has a good fit.